2022
DOI: 10.1002/bit.28197
|View full text |Cite
|
Sign up to set email alerts
|

Recent developments in cell shipping methods

Abstract: As opposed to remarkable advances in the cell therapy industry, research reveal inexplicable difficulties associated with preserving and post‐thawing cell death. Post cryopreservation apoptosis is a common occurrence that has attracted the attention of scientists to use apoptosis inhibitors. Transporting cells without compromising their survival and function is crucial for any experimental cell‐based therapy. Preservation of cells allows the safe transportation of cells between distances and improves quality c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 147 publications
0
2
0
Order By: Relevance
“…Due to the resemblance between biofilms and encapsulated systems, our method is also potentially applicable to biofilm or granular systems for quantifying colonies across depth. Such advances could greatly enhance our understanding of microbial colony formation across spatial and temporal scales, expanding predictable environmental engineering applications of both encapsulated and biofilm systems in contaminant remediation (Cassidy et al, 1996 ; Wang et al, 2021 ), resource recovery (Chen et al, 2021 ), and cell preservation and transportation (Heydarzadeh et al, 2022 ). Overall, this method represents a contribution that should facilitate better prediction and greater understanding of how encapsulated microbes grow.…”
Section: Resultsmentioning
confidence: 99%
“…Due to the resemblance between biofilms and encapsulated systems, our method is also potentially applicable to biofilm or granular systems for quantifying colonies across depth. Such advances could greatly enhance our understanding of microbial colony formation across spatial and temporal scales, expanding predictable environmental engineering applications of both encapsulated and biofilm systems in contaminant remediation (Cassidy et al, 1996 ; Wang et al, 2021 ), resource recovery (Chen et al, 2021 ), and cell preservation and transportation (Heydarzadeh et al, 2022 ). Overall, this method represents a contribution that should facilitate better prediction and greater understanding of how encapsulated microbes grow.…”
Section: Resultsmentioning
confidence: 99%
“…Our previous study demonstrated that Wharton’s jelly-derived mesenchymal stem cells (WJ-MSCs) transfected with apelin can promote rat pancreatic β-cell proliferation and maintain long-term glucose stability [ 12 ]. However, cell therapy has several limitations, including preservation challenges and stability issues [ 13 ]. Furthermore, the introduction of WJ-MSCs into the human body poses the potential risk of adverse effects from cell proliferation [ 14 ].…”
Section: Introductionmentioning
confidence: 99%